The 14th colony - Berry, Steve, 1955- (Berry, Steve, 1955- Cotton Malone novels., 2016)
"What happens if both the president and vice-president-elect die before taking the oath of office? The answer is far from certain--in fact, what follows would be nothing short of total political chaos. Shot down over Siberia, ex-Justice Department agent Cotton Malone is forced into a fight for survival against Aleksandr Zorin, a man whose loyalty to the former Soviet Union has festered for decades into an intense hatred of the United States. Before escaping, Malone learns that Zorin and another ex-KGB officer, this one a sleeper still embedded in the West, are headed overseas to Washington D.C. Inauguration Day--noon on January 20th--is only hours away. A flaw in the Constitution, and an even more flawed presidential succession act, have opened the door to disaster and Zorin intends to exploit both weaknesses to their fullest. Armed with a weapon leftover from the Cold War, one long thought to be just a myth, Zorin plans to attack. He's aided by a shocking secret hidden in the archives of America's oldest fraternal organization--the Society of Cincinnati--a group that once lent out its military savvy to presidents, including helping to formulate three invasion plans of what was intended to be America's 14th colony--Canada. In a race against the clock that starts in the frozen extremes of Russia and ultimately ends at the White House itself, Malone must not only battle Zorin, he must also confront a crippling fear that he's long denied, but which now jeopardizes everything. Steve Berry's trademark mix of history and speculation is all here in this provocative new thriller"--